Uncovering the Identity Conditions of High School Students - Gusti Rahayu; Herman Nirwana; Netrawati Netrawati (International Journal of Applied Counseling and Social Sciences, 2020)
This study aims to analyze the identity of high school students based on four levels of status (identity diffusion, identity foreclosure, identity moratorium, and identity achievement). Self-identity is very important because the task of development at that time is to adapt to changes that exist in oneself. Teens who experience an identity crisis show that they are trying to find their identity. Therefore, adolescents need help to improve their identity. This study aims to describe the identity of students. The sample in this study consisted of 240 high school students who were selected by proportional random sampling. The instrument used was a self-identity scale. The instrument used has been tested for validity and reliability. Data analysis in this study used a quantitative approach with descriptive methods. The results showed that identity diffusion was in the high category 33.85 (81 students), identity foreclosure was in the high category 10.8% (26 students), identity moratorium was in the high category 46.2% (111 students), and identity achievement was at high category 9.3% (22 students). The implication of this research is the counselor's basis for improving the self-identity of students in schools